The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2214/ajr.17.18879
|View full text |Cite
|
Sign up to set email alerts
|

Overutilization of Health Care Resources for Breast Pain

Abstract: Breast pain represents an area of overutilization of health care resources. For female patients who present with pure breast pain, breast imaging centers should consider the following imaging protocols and education for referring physicians: an annual screening mammogram should be recommended for women 40 years or older, and reassurance without imaging should be offered to patients younger than 40 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Inevitably, performing imaging investigations in this cohort of women will result in "false positive" findings; the discovery of benign lesions that would never have caused any symptoms. These are seen in around 5% of women with breast pain alone 27 and when discovered instigate further intervention. In our cohort, 77 women (4%) suffered the prolonged anxiety of awaiting further investigations and (eventually benign) results, with others reporting similar rates 27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inevitably, performing imaging investigations in this cohort of women will result in "false positive" findings; the discovery of benign lesions that would never have caused any symptoms. These are seen in around 5% of women with breast pain alone 27 and when discovered instigate further intervention. In our cohort, 77 women (4%) suffered the prolonged anxiety of awaiting further investigations and (eventually benign) results, with others reporting similar rates 27 .…”
Section: Discussionmentioning
confidence: 99%
“…These are seen in around 5% of women with breast pain alone 27 and when discovered instigate further intervention. In our cohort, 77 women (4%) suffered the prolonged anxiety of awaiting further investigations and (eventually benign) results, with others reporting similar rates 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eliminating the number of low yield follow‐up studies would decrease cost. Kushwaha et al found a single complete breast ultrasound (CPT code 76641) costs $150.59 26 . With three follow‐up studies typically performed for a BI‐RADS 3 assessment, the healthcare cost may potentially deter patients from completing their full 24‐month surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with potentially resectable PDAC, MR with diffusion weighted sequences (DWI) significantly improved the diagnostic performance in the characterization of focal liver lesions, especially if small (≤1 cm), as compared with CT. In particular, MR after CT plays a role on liver staging [ 17 ] ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%